Pulau Sebatik Pulau yang Dua Negara yang Terpinggir di Malaysia - Ramli Dolah, Ahmad Sahide, Nordin Sakke, Mustapa Abd.Talip, Wan Shawaluddin Wan Hassan (LP3M UMY, 2018)
Buku ini berisi tentang pulau Sebatik